2020
DOI: 10.1103/physrevlett.124.014501
|View full text |Cite
|
Sign up to set email alerts
|

Critical Point for Bifurcation Cascades and Featureless Turbulence

Abstract: In this Letter we show that a bifurcation cascade and fully sustained turbulence can share the phase space of a fluid flow system, resulting in the presence of competing stable attractors. We analyse the toroidal pipe flow, which undergoes subcritical transition to turbulence at low pipe curvatures (pipe-to-torus diameter ratio) and supercritical transition at high curvatures, as was previously documented. We unveil an additional step in the bifurcation cascade and provide evidence that, in a narrow range of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Furthermore, concomitant scenarios of bypass and classical transition have been observed on longer timescales, and their possibly simultaneous occurrence blurs the long-time output of the edge tracking algorithm. To our knowledge, whereas instances of such a coexistence have been reported in more complicated geometries (Xu et al 2017;Canton et al 2019) this coexistence is reported for the first time that in a simulation of an unforced boundary layer flow. A moving box technique allows for a more efficient usage of the computational domain.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, concomitant scenarios of bypass and classical transition have been observed on longer timescales, and their possibly simultaneous occurrence blurs the long-time output of the edge tracking algorithm. To our knowledge, whereas instances of such a coexistence have been reported in more complicated geometries (Xu et al 2017;Canton et al 2019) this coexistence is reported for the first time that in a simulation of an unforced boundary layer flow. A moving box technique allows for a more efficient usage of the computational domain.…”
Section: Discussionmentioning
confidence: 48%
“…Global methods can, however, fall short whenever no available global observable can elucidate on which side of the edge the different trajectories evolve [31,73], when one of the attractors undergoes a local bifurcation affecting the values of the bounds [74] or simply when information on the bounds α A,B is not available.…”
Section: A Global Versus Local Methodsmentioning
confidence: 99%
“…The three canonical cases of curved pipe flow, plane channel flow and the Blasius boundary layer have been assessed numerically in very recent investigations. For curved pipe flow finite curvature leads, above some threshold in the Reynolds number, to an additional instability absent from the straight pipe case [25]. This instability leads to a limit cycle replacing the laminar state.…”
Section: Introductionmentioning
confidence: 97%